The application of theories in edutourism research: a systematic literature review - Sinoretha Sining; Velan Kunjuraman (Penerbit Universiti Kebangsaan Malaysia, 2025)
A systematic literature review was conducted to address the gap in understanding how theory is applied within the growing field of edutourism research. Adhering to PRISMA guidelines, we analysed 68 journal articles and classified them by their theoretical approaches and research themes. A primary finding was that a significant portion of studies currently lack a specific theoretical framework. A key insight was that those studies that do implement theory achieve a higher average weighted citation impact, suggesting a clear link between a strong theoretical foundation and academic influence. The review successfully identified 12 distinct theories employed in the literature, with Experiential Learning Theory being the most dominant and frequently used framework. Our analysis also revealed no statistically significant association between a study's specific theme, such as cultural, environmental, or academic tourism and its chosen theoretical approach. This suggests that the research topic does not limit the consistent application of theory. Theseresults collectively highlight a critical need for a more robust theoretical foundation in edutourism research to enhance its overall academic credibility and influence. This study offers an in-depth evaluation of the current state of theory use and serves as a call for future research to be more explicitly guided by theoretical frameworks, thereby advancing the field as a whole.